2013
DOI: 10.1073/pnas.1213923110
|View full text |Cite
|
Sign up to set email alerts
|

Stress increases aversive prediction error signal in the ventral striatum

Abstract: From job interviews to the heat of battle, it is evident that people think and learn differently when stressed. In fact, learning under stress may have long-term consequences; stress facilitates aversive conditioning and associations learned during extreme stress may result in debilitating emotional responses in posttraumatic stress disorder. The mechanisms underpinning such stress-related associations, however, are unknown. Computational neuroscience has successfully characterized several mechanisms critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 33 publications
11
80
1
1
Order By: Relevance
“…This idea could help explain why anxiety improves performance at both encoding and retrieval: when reencountering a threatening environment it is of extra importance to remember the prior locations of potential threats. In line with this suggestion, prior research has demonstrated that threat increases aversive prediction error signal in the ventral striatum, indicating that anxiety may bias the predictive learning of threats to promote survival (Robinson et al 2013a). In the context of anxiety disorders, however, it may be that these responses are exaggerated and/or perpetual, thus contributing to the maintenance of an anxious state (Liberzon and Abelson 2016); this proposal is in line with the finding that visual working memory capacity increases as trait anxiety increases (Moriya and Sugiura 2012).…”
Section: Visuospatial Working Memorysupporting
confidence: 49%
“…This idea could help explain why anxiety improves performance at both encoding and retrieval: when reencountering a threatening environment it is of extra importance to remember the prior locations of potential threats. In line with this suggestion, prior research has demonstrated that threat increases aversive prediction error signal in the ventral striatum, indicating that anxiety may bias the predictive learning of threats to promote survival (Robinson et al 2013a). In the context of anxiety disorders, however, it may be that these responses are exaggerated and/or perpetual, thus contributing to the maintenance of an anxious state (Liberzon and Abelson 2016); this proposal is in line with the finding that visual working memory capacity increases as trait anxiety increases (Moriya and Sugiura 2012).…”
Section: Visuospatial Working Memorysupporting
confidence: 49%
“…The ventral portions of the caudate, including the accumbens, have traditionally been associated with transient, reward-related processes (Haber and Knutson, 2009), but recent more research has suggests a potential role for the nucleus accumbens during aversive processing (Becerra et al, 2001; Cabib and Puglisi-Allegra, 1994, 1996; Delgado et al, 2008; Jensen et al, 2003; McMenamin et al, 2014; Oleson et al, 2012; Robinson et al, 2013; Salamone, 1994; Schoenbaum and Setlow, 2003). Critically, this accumbens region of interest may have gone unnoticed if common data analysis strategies were used to search for connectivity changes (such as using amygdala-based seed analysis).…”
Section: Discussionmentioning
confidence: 99%
“…However, as fMRI activation in the VS has also been shown to respond to non-rewarding events such as negative outcomes or saliency (Jensen et al, 2007; Menon et al, 2007; Litt, Plassmann, Shiv, & Rangel, 2011; Metereau & Dreher, 2013; Robinson, Overstreet, Charney, Vytal, & Grillon, 2013; Seymour et al, 2004; Zink, Pagnoni, Chappelow, Martin-Skurski, & Berns, 2006), this approach has to be interpreted with extreme care (Poldrack, 2006) and should always be accompanied by behavioral measures of reinforcer value.…”
Section: Ventral Striatal Activation In Reward Learningmentioning
confidence: 99%